Autologous stem cell transplant in recurrent or refractory primary or secondary central nervous system lymphoma using thiotepa, busulfan and cyclophosphamide. Issue 2 (February 2015) - Welch, Mary R.; Sauter, Craig S.; Matasar, Matthew J.; Faivre, Geraldine; Weaver, Susan A.; Moskowitz, Craig H.; Omuro, Antonio M.
Abstract The prognosis for patients with central nervous system (CNS) involvement by recurrent or refractory diffuse large B-cell lymphoma is poor, with overall survival (OS) of 4–10 months. High-dose chemotherapy (HDC) and autologous stem cell transplant (ASCT) is a potential treatment alternative. We reviewed patients with recurrent primary (PCNSL) or secondary (SCNSL) CNS lymphoma referred for consolidation HDC-ASCT utilizing thiotepa, busulfan and cyclophosphamide (TBC). Among the 17 patients included, all had achieved a complete remission after salvage induction chemotherapy, which incorporated methotrexate in 82% of patients. Two patients failed stem-cell harvesting and 15 (88%) underwent transplant. The estimated 3-year progression-free survival (PFS) and OS were both 93% (95% confidence interval 61–99%). Median PFS and OS were not reached. There was no transplant-related mortality. These results confirm the benefit of TBC followed by ASCT in select patients with recurrent PCNSL and suggest a potential role for the regimen in those with SCNSL. Further investigation is warranted.